The Acceptability of Pre-Exposure Prophylaxis: Beliefs of Health-Care Professionals Working in Sexually Transmitted Infections Clinics and HIV Treatment Centers - Janneke P. Bil; Elske Hoornenborg; Elske Hoornenborg; Maria Prins; Maria Prins; Arjan Hogewoning; Arjan Hogewoning; Fernando Dias Goncalves Lima; Henry J. C. de Vries; Henry J. C. de Vries; Henry J. C. de Vries; Henry J. C. de Vries; et al. (Frontiers Media S.A., 2018)
BackgroundPre-exposure prophylaxis (PrEP) is highly effective for preventing HIV infections, but is not yet implemented in the Netherlands. As the attitudes of health-care professionals toward PrEP can influence future PrEP implementation, we studied PrEP knowledge and beliefs and their association with PrEP acceptability among professionals in clinics for sexually transmitted infection (STI professionals) and HIV treatment centers (HIV specialists). In addition, we examined preferred regimens, attitudes toward providing PrEP to key populations and to reimbursement of PrEP costs.MethodsAn online questionnaire was distributed among 24 public health STI clinics and 27 HIV treatment centers nationwide in the Netherlands between January and August 2015. The acceptability of PrEP was measured on a 7-point Likert scale ranging from 1 = low to 7 = high acceptability. Univariable and multivariable linear regression analyses were used to explore associations between demographic characteristics, PrEP knowledge, beliefs about PrEP, and PrEP acceptability.ResultsIn total, 209 people (143 STI professionals and 66 HIV specialists) completed the questionnaire. The mean acceptability of PrEP implementation was 4.28 (SD 1.68) among STI professionals and 4.42 (SD 1.67) among HIV specialists. The mean score on self-perceived knowledge related to PrEP efficacy was 3.90 (SD 1.57) among STI professionals and 5.68 (SD 1.08) among HIV specialists (p-value of <0.001). Beliefs associated with lower PrEP acceptability among both groups were the fear that PrEP use will lead to a decrease in condom use and an increase in STI, the high costs of PrEP and ethical issues regarding prescribing antiretroviral medication to healthy individuals. No preference for a daily or an event-driven regimen was detected. Most participants deemed the following groups to be eligible for PrEP: men who have sex with men (MSM) who regularly get post-exposure prophylaxis, MSM who never used condoms with casual partners and MSM with an HIV-positive partner with a detectable viral load. Over half of the participants indicated that PrEP users should partly (54.1%) or fully (35.4%) pay the costs of PrEP.ConclusionIn 2015, PrEP acceptability was only moderate among Dutch STI professionals and HIV specialists, which is far from an optimal setting. Addressing barriers to PrEP acceptability in educational programs for various types of health-care professionals is needed to successfully implement PrEP in the Netherlands.